Proactive telephone-based peer support for breastfeeding: a cross-sectional survey of women's experiences of receiving support in the RUBY randomised controlled trial. Issue 10 (30th October 2020) - McLardie-Hore, Fiona E; McLachlan, Helen L; Shafiei, Touran; Forster, Della A
Abstract : Objective: The Ringing Up about Breastfeeding earlY (RUBY) randomised controlled trial (RCT) of proactive telephone-based peer support for breastfeeding found that infants of women allocated to the intervention were more likely to be receiving breast milk at 6 months of age than those receiving usual care. This study explores women's experiences of receiving the RUBY peer support intervention. Design: Cross-sectional survey. Setting: Women were recruited from the postnatal units of three tertiary hospitals in Melbourne, Australia. Participants: Women allocated to receive telephone peer support in the RUBY RCT who completed a telephone interview at 6 months postpartum (501/574 (87%) in trial intervention arm) were invited to complete a postal survey on their experience of receiving support. Outcomes: Experiences of support from the allocated peer, perceived helpfulness, topics discussed, overall satisfaction with the support and frequency and duration of contact were explored. Results: Surveys were sent between August 2013 and March 2016, and 72% (360/501) responded of whom 341 recalled receiving peer support. Women reported high levels of perceived helpfulness (79%) and overall satisfaction with the peer support (93%). Discussions included breastfeeding topics (milk supply, attachment), baby care, baby behaviour, and reassurance and emotional support. Women valued the practical and realistic support from another mother, as well as the proactive nature, continuity and accessibility of the support. The empathy, reassurance and encouragement provided helped the mothers to 'cope', to continue breast feeding and to feel empowered. Conclusion: Most respondents were positive about their experience of receiving proactive telephone peer support for breastfeeding, further supporting the roll-out of this model as a strategy for increasing breastfeeding maintenance to 6 months. Recommendations include flexibility in the scheduling of calls according to individual need, and the use of text messages in conjunction with proactive calls, to enhance and facilitate communication between the peer and the mother. Trial registration number: ACTRN12612001024831.